2002
DOI: 10.1007/s00040-002-8306-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of wax by virgin queens of the stingless bee Melipona bicolor (Apidae, Meliponinae)

Abstract: Young virgin queens of the stingless beeMelipona bicolor have been shown to produce wax like workers. The small, white to transparent flakes of wax of the queens protrude from the intersegmental space and cover the anterior part of the tergite cuticle, in a way similar to that in workers. This points to the presence of wax glands in the queens. However, workers produce wax from glands located at the fourth to seventh tergites whereas queens secrete wax from the epidermal gland at the third tergite only. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Even fewer studies focus on waxes of other bees. Blomquist et al (Blomquist et al, 1985) analyzed the chemical composition of Trigona (Trigonisca) buyssoni (Fabricius) and Trigona (Trigonisca) atomaria (Ducke) waxes, Milborrow et al (Milborrow et al, 1987) analyzed Trigona australis (Smith), and Koedam et al (Koedam et al, 2002) examined the wax of Melipona bicolor (Lepeletier). The primary components of beeswaxes include alkanes, fatty acids and long-chain esters (Tulloch, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Even fewer studies focus on waxes of other bees. Blomquist et al (Blomquist et al, 1985) analyzed the chemical composition of Trigona (Trigonisca) buyssoni (Fabricius) and Trigona (Trigonisca) atomaria (Ducke) waxes, Milborrow et al (Milborrow et al, 1987) analyzed Trigona australis (Smith), and Koedam et al (Koedam et al, 2002) examined the wax of Melipona bicolor (Lepeletier). The primary components of beeswaxes include alkanes, fatty acids and long-chain esters (Tulloch, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The production of wax by meliponine virgin queens was observed in Melipona bicolor (Koedam et al 2002), but not in the species examined in this study. Nevertheless, the production of wax, and even its manipulation (ImperatrizFonseca 1973) in meliponines may be more frequent than it was though.…”
Section: Resultsmentioning
confidence: 75%
“…The production of wax by virgin queens has been reported by some authors (Ihering 1903, Koedam et al 2002 and ImperatrizFonseca (1973) observed young virgin queens of Schwarziana quadripunctata Lepeletier, building wax alveoli, supporting a wax production function for these glands in the virgin queens, although wax production and manipulation for building the nest is a typical worker task.…”
Section: Tegumentary Epithelial Glands In the Abdomen Of Virgin And Pmentioning
confidence: 99%
“…Pure oleic acid and methyl oleate were available for comparison. Triacontanyl acetate from the wax of Melipona bicolor (Koedam et al, 2002) was heated at 50…”
Section: Chemical Analysismentioning
confidence: 99%